1996
DOI: 10.1016/s0022-5347(01)65751-3
|View full text |Cite
|
Sign up to set email alerts
|

PAX-2: A Developmental Gene Constitutively Expressed in the Mouse Epididymis and Ductus Deferens

Abstract: Pax-2 is a transcriptional regulator expressed in the epithelium of the ductus deferens and epididymis and may be a regulator of epithelial genes involved in sperm maturation and support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2000
2000
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…We found that AmphiPax2/5/8 was expressed in the testis and tail. Similarly in vertebrates, early discoveries disclosed the expression of Pax2 in the vas deferens and epididymis [30,31], and the expression of Pax5 in both the testis and chordoneural hinge region of the tail [32,33]. Integratively considering all of these observations, we presume that AmphiPax2/5/8 is a multi-function gene in amphioxus and it is subfunctionalized after gene duplication in vertebrates.…”
Section: Conserved Roles Of Pax2/5/8 Subfamily Genesmentioning
confidence: 74%
“…We found that AmphiPax2/5/8 was expressed in the testis and tail. Similarly in vertebrates, early discoveries disclosed the expression of Pax2 in the vas deferens and epididymis [30,31], and the expression of Pax5 in both the testis and chordoneural hinge region of the tail [32,33]. Integratively considering all of these observations, we presume that AmphiPax2/5/8 is a multi-function gene in amphioxus and it is subfunctionalized after gene duplication in vertebrates.…”
Section: Conserved Roles Of Pax2/5/8 Subfamily Genesmentioning
confidence: 74%
“…aquaporin-1 with its role in fluid resorption, it would appear that epididymal epithelial cells have defined functions prior to birth (Fisher et al, 1998). Null mutation and tissue distribution studies have indicated that normal development of the epididymis during gestation is crucially dependent on the presence of several genes, including the growth factor Bmp8a (Zhao et al, 1998), the oncogene e-ros (Sonnenberg-Riethmacher et al, 1996), the paired box gene Pax-2 (Oefelein et al, 1996), and the homeobox domain related genes, Hox family of genes (Podlasek et al, 1999;Lindsey et al, 1996), and Pem2 (Sutton et al, 1998). …”
Section: Differentiation: the Formation Of The Epididymal Ductmentioning
confidence: 99%
“…As in the Wolffian tubes and the developing kidneys, 16,17 PAX2 is detected in the Mü llerian ducts and its derivatives in mice. 18 However, information on the function and the clinical significance of PAX2 in the human Mü llerian system is sparse 19,20 in contrast to what is known about its role in renal development.…”
mentioning
confidence: 99%